Study of particle number size distributions at Azadi terminal in Tehran, comparing high-traffic and no traffic area - Ramin Nabizadeh (MethodsX, 2018)
Vehicle traffic is known as the anthropogenic aerosol source in megacities. Exposure to ambient air pollution, especially particulate matter has become the most environmental risk factor. The main aim of this study is to determine the particle number and their size distribution in Tehran at Azadi terminal (located in the West of Tehran), crossing of Nawab and Azadi streets the area with high traffic, and campus of Tehran University as an area without traffic. Particle size distribution (0.3–1 μm) was measured using a Grimm Environmental Dust Monitor and was conducted in two seasons, hot and cold (summer 2016 and winter 2016). The measurement was performed twice per month. Although the average number of particles at Azadi Terminal was more than the other two locations in both seasons but it was not significant) p > 0.05). The average number of particles larger than 0.3 μm was 286.72 ± 129.55 and 183.61 ± 86.79 cm−3 in winter and summer respectively. In relation to particles size distribution, the average number of particles larger than 0.4, 0.5, 0.65, 0.8 and 1 μm in winter and summer were 111.5 ± 120, 29.3 ± 23.7, 8.2 ± 5.8, 4 ± 3, 2 ± 1.5 and 52.5 ± 37, 14.4 ± 10.8, 6.1 ± 5, 3.8 ± 3.5, 2.3 ± 2 cm−3 respectively. In the current study the highest number of particles significantly observed in winter time in comparison to summer. In addition, had no significant difference between the number of particles at three sampling locations. Keywords: PM, Traffic, Size distribution, Iran